Analiza ukrepov za zmanjšanje flikerja v prenosnem omrežju Slovenije - Blažič, Boštjan (Elektrotehniški vestnik, 2008)
In the paper we evaluate different solutions for mitigating fliker which is giving rise to serious problems in the Slovenian transmission network. Fliker, which is known to be one of the major disturbances affecting the voltage quality, is in Slovenia caused by three large arc furnaces located at the ironworks of Jesenice, Ravne and Štore. According to the standard SIST EN 50160 1, fliker at the transmission level makes it difficult, or even impossible, to maintain an adequate voltage quality at the distribution level.In order to solve the issue, we started by implementing in PSCAD a simulation model of the Slovenian transmission network (Fig. 1). Additionally to the basic network elements we also developed an arc furnace model and an IEC flicker meter model 2 - 4. To allow for flicker compensation, we used our static var compensator (SVC) and static compensator (STATCOM) mcidels (Figs. 2 and 3). With the network model we tried to capture as much as possible of the real network conditions 2. Thus obtained flicker values are given in the first column of Table 1. Solutions enabling flicker mitigation can be divided into two groups, Le. system solutions and compensation solutions. The first group involves changes in the network topology and network elements, whereas the second group foresees solutions achieved by using devices permitting compensation of the fluctuating reactive power. By using STATCOM for the case of the Ravne arc-furnace compensation (Fig. 4) 5,the reactive power from the network is close to zero. The ultimate result is reduced fluctuation of the network voltage and consequently also lower flicker. In our investigation of the possible measures for flicker mitigation,we took into account also the cost and practical feasibility aspects of the various available solutions.
Keywords: električna omrežja; nihanje napetosti; prenosno omrežje; statični kompenzatorji; serijska dušilka; fliker